2004
DOI: 10.1002/hed.10352
|View full text |Cite
|
Sign up to set email alerts
|

A case of radiation recall mucositis associated with docetaxel

Abstract: Background. Radiation recall reactions, in particular dermatitis, are well documented in the literature. However, radiation recall mucositis is a rare clinical phenomenon.Methods. We report a case of a 45-year-old man diagnosed with squamous cell carcinoma of the base of tongue. He was treated with surgery followed by chemotherapy and radiation therapy. Several months after completing treatment, he had a recurrence develop outside of the previously irradiated field. He was offered radiation therapy concurrent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 17 publications
1
6
0
Order By: Relevance
“…Mostly previous studies have reported that RRD occurs with lower energy photon beams, [ 13 , 14 ] and RRD with 10-MV photon beam, as observed in our patient, is relatively rare. Radiation doses at the skin surface with the 10-MV photon beam were less than 6-MV photon beams.…”
Section: Discussionsupporting
confidence: 65%
“…Mostly previous studies have reported that RRD occurs with lower energy photon beams, [ 13 , 14 ] and RRD with 10-MV photon beam, as observed in our patient, is relatively rare. Radiation doses at the skin surface with the 10-MV photon beam were less than 6-MV photon beams.…”
Section: Discussionsupporting
confidence: 65%
“…A third reason for the toxicity could be the second-line chemotherapy started 1 month before the esophageal fistula, which may have caused a recall phenomenon in the esophageal mucosa. (11) After accounting for all possible factors, it is most likely that the high esophageal PBT dose is the main reason for this late esophageal toxicity. In fact, the esophageal dose in other patients without esophageal late toxicities did not exceed 74 Gy (RBE).…”
Section: Discussionmentioning
confidence: 99%
“…Radiation recall myositis is most commonly associated with gemcitabine, [8][9][10] which is also Practical Radiation Oncology: January-February 2020 Radiation recall myositis in the thigh known to induce a myositis syndrome by itself. 11 Docetaxel has been identified as the offending agent in other types of radiation recall reactions [12][13][14][15][16][17][18] but has not been seen to cause radiation recall myositis. Radiation recall myositis has been observed in 1 case in a patient treated with carboplatin/paclitaxel 19 but has not been seen with the combination of a platinum agent with docetaxel.…”
Section: Radiation Recall Myositismentioning
confidence: 99%